2013
DOI: 10.1556/achrom.25.2013.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of flavonoids inScutellaria incanaL. using LC-Q-TOF-MS

Abstract: Summary. Scutellaria L. is a diverse genus of the Lamiaceae (Labiatae) family of over 300 herbaceous plants commonly known as skullcaps. Various species of Scutellaria are used as ethnobotanical herbs for the treatment of ailments like cancer, jaundice, cirrhosis, anxiety, and nervous disorders. Scutellaria incana L., commonly known as the Hoary skullcap, is a traditional medicinal plant used by native Americans as a sedative for nervousness or anxiety. S. incana metabolites were identified by comparing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In the case of compounds (2) and (3) , UV spectra were identical with flavone monoglucoside ( 22 ), which was supported by 1 H-NMR and 13 C-NMR spectrums, showing characteristic signals appeared at δ H 6.70 (1H, s, H-3), 6.62 (1H, s, H-3), indicating the chromophore are flavones, luteolin, and apigenin, respectively. A literature survey indicated that luteolin-7-o-ß-D-glucoside (2) and apigenin-7-o-ß-D-glucoside (3) have previously been isolated from Scutellaria genus ( 23 24 ). The UV spectroscopic data of compound (4) revealed its phenolic nature.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of compounds (2) and (3) , UV spectra were identical with flavone monoglucoside ( 22 ), which was supported by 1 H-NMR and 13 C-NMR spectrums, showing characteristic signals appeared at δ H 6.70 (1H, s, H-3), 6.62 (1H, s, H-3), indicating the chromophore are flavones, luteolin, and apigenin, respectively. A literature survey indicated that luteolin-7-o-ß-D-glucoside (2) and apigenin-7-o-ß-D-glucoside (3) have previously been isolated from Scutellaria genus ( 23 24 ). The UV spectroscopic data of compound (4) revealed its phenolic nature.…”
Section: Discussionmentioning
confidence: 99%
“…Based on fragmentation spectra, accurate mass and previous literature reports, compound 13 was tentatively identified as chrysin-7-glucuronide. 111 Compound 14 (peak 14) possessed molecular ion [M–H] − at m / z 461. Furthermore, the fragment ion at m / z 299 corresponds to the loss of glucose moiety, indicating the molecular ion of peonidin aglycone.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks observed in the chromatograms of the TGY samples were primarily identified based on a comparison of their accurate molecular mass data with those of the reference standards and data from the literature [ 19 23 ]. In this way, we were able to identify 28 compounds.…”
Section: Resultsmentioning
confidence: 99%